Imploding Populations in Japan and Germany : a Comparison - Coulmas, Florian; Lützeler, Ralph (International comparative social studies ;, 2011)
This book provides a comprehensive overview of the impact of low birth-rates and population decline on Japan and Germany. Experts from both countries examine a broad range of issues, from demographic change, social ageing, family policies, family formation, work-life balance, domestic and international migration to business perspectives and labour market issues. Focussed on Japan and Germany, two highly developed countries with extremely low fertility, the chapters of this volume also refer to several other countries for comparison. In the absence of war, famine and pandemics, rapid population.